A green and non-corrosive rubber-plastic thermal insulation material and preparation method thereof
By using raw materials such as nitrile rubber and EVA combined with maleic anhydride-grafted PE, a green and non-corrosive rubber-plastic thermal insulation material was prepared, which solved the problem of metal corrosion caused by chloride ions and elemental sulfur, and achieved the material's non-corrosiveness and good comprehensive performance.
Patent Information
- Application Number
- CN202411254374.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-09
AI Technical Summary
Existing rubber and plastic insulation materials contain chloride ions and elemental sulfur, which cause metal corrosion problems and cannot completely solve the problem of metal corrosion.
Using nitrile rubber and EVA as aggregates, combined with maleic anhydride-grafted PE, composite accelerators and composite flame retardants, a green and non-corrosive rubber-plastic insulation material is prepared through specific mixing and foaming processes, avoiding the presence of chloride ions and elemental sulfur.
This technology ensures that rubber and plastic insulation materials are free of chloride ions and elemental sulfur, preventing metal corrosion and maintaining properties such as low thermal conductivity, fire resistance, and moisture resistance, thus extending the service life of products or equipment.
Smart Images

Figure CN118755166B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber-plastic thermal insulation materials, and in particular to a green, non-corrosive rubber-plastic thermal insulation material and a preparation method thereof. Background Art
[0002] Rubber-plastic insulation material is an elastic closed-cell foam material with low thermal conductivity, fire retardancy, moisture resistance and humidity resistance. It is widely used in central air-conditioning, construction, chemical industry, electrical appliances and other related hot and cold medium pipes or containers, and most of the above pipes or containers are made of metal.
[0003] Most common rubber and plastics are made of NBR / PVC blends, which are made by sulfur vulcanization and foaming. The products contain a large amount of chloride ions and elemental sulfur. The interaction between chloride ions and metals can cause electrochemical reactions on the metal surface, thereby causing metal corrosion. In addition, chloride ions and metals can also form metal ion and chloride ion coordination compounds, which are also important causes of metal corrosion. Elemental sulfur has the characteristic of being sublimable, and sublimation into the air will corrode metal products such as copper and silver.
[0004] Generally speaking, in order to achieve good protection effects, rubber-plastic insulation materials will directly contact pipes and air ducts, so their chloride ions and elemental sulfur will bring a greater risk of metal corrosion, thereby shortening the service life of the product or equipment.
[0005] The patent with publication number CN108034094A discloses a sulfur-free rubber-plastic thermal insulation material and a preparation method thereof, wherein the components thereof are nitrile rubber, polyvinyl chloride, chlorinated polyethylene, azodicarbonamide, antimony trioxide, N-phenylene maleimide, talcum powder, dioctyl ester, zinc oxide, carbon black, antioxidant, chlorinated paraffin and stearic acid. Although the product does not contain sulfur, the components thereof include polyvinyl chloride, chlorinated polyethylene, chlorinated paraffin and other substances containing chlorine, and the product will contain a large amount of chloride ions. Although there is no sulfur, it will still corrode metals.
[0006] The patent with publication number CN113621185A discloses a halogen-free rubber-plastic thermal insulation material and a preparation method thereof, wherein the components thereof include 0.2%-0.4% sulfur, 0.25%-0.35% zinc benzenesulfinate, 0.5%-2.5% accelerator pz, and 0.2%-0.75% accelerator DPTT. The sulfur vulcanization system used therein contains elemental sulfur which does not participate in the vulcanization reaction.
[0007] It can be seen that although there are products that do not contain chloride ions or elemental sulfur, they can only limit one element, so they cannot completely solve the problem of rubber and plastic products corroding metals. Therefore, how to ensure that the rubber and plastic products have low thermal conductivity, fire retardant, moisture and humidity resistance, and at the same time, make them free of chloride ions and elemental sulfur, so as to completely solve the problem of rubber and plastic products corroding metals, is one of the new directions in the research and development of rubber and plastic materials. Summary of the invention
[0008] The purpose of the present invention is to provide a green non-corrosive rubber-plastic thermal insulation material and a preparation method thereof. The method uses nitrile rubber and EVA as aggregates, and realizes the preparation of a green non-corrosive rubber-plastic thermal insulation material with good comprehensive performance through the use of maleic anhydride grafted PE, a composite accelerator, and a composite flame retardant, and completely solves the problem of metal corrosion by rubber and plastic products.
[0009] The green non-corrosive rubber-plastic thermal insulation material of the present invention comprises the following raw materials in parts by weight:
[0010] 13-16.5 parts of nitrile rubber, 8-10.5 parts of EVA, 9-13 parts of azodicarbonamide, 9-12 parts of maleic anhydride grafted PE, 1.5-3.5 parts of carbon black, 0.3-0.5 parts of stearic acid, 0.2-0.5 parts of calcium stearate, 0.1-0.3 parts of zinc oxide, 1.5-2.5 parts of vulcanizing agent, 2-3 parts of polyethylene glycol, 2-3.5 parts of paraffin, 1-3 parts of paraffin oil, 0.2-0.5 parts of antioxidant, 0.3-0.6 parts of accelerator, 36-46 parts of flame retardant;
[0011] The flame retardant comprises the following raw materials in parts by weight: 1-3 parts of antimony trioxide, 15-18 parts of methyl dimethyl phosphate, and 20-25 parts of aluminum hydroxide.
[0012] Furthermore, the mass ratio of the nitrile rubber to the EVA is (2-3):(1.5-2).
[0013] Furthermore, the VA content of the EVA is 12% to 16%.
[0014] Furthermore, the antioxidant is antioxidant 4010.
[0015] Furthermore, the vulcanizing agent is BIPB.
[0016] Furthermore, the accelerator is one or both of accelerator DB and accelerator DM.
[0017] Furthermore, the accelerator is composed of accelerator DB and accelerator DM in a mass ratio of 2:1.
[0018] Another object of the present invention is to provide a method for preparing the green, non-corrosive rubber-plastic thermal insulation material, which specifically comprises the following steps:
[0019] S1, putting nitrile rubber, EVA, and maleic anhydride grafted PE into an internal mixer for primary mixing, then putting antimony trioxide, carbon black, stearic acid, calcium stearate, methyl dimethyl phosphate, polyethylene glycol, antioxidant, aluminum hydroxide, BIPB, and paraffin into an internal mixer for secondary mixing, finally mixing azodicarbonamide and paraffin oil for a third time, then discharging, opening the mixer for tabletting and cooling to obtain material No. 1;
[0020] S2, putting the No. 1 material into an internal mixer, adding zinc oxide and accelerator, mixing and mixing, and then entering an open mixer, cutting into strips to obtain No. 2 material;
[0021] S3, extruding and molding the No. 2 material, foaming it, and cooling it to obtain a green, non-corrosive rubber-plastic thermal insulation product.
[0022] Furthermore, the first mixing time is 1 to 3 min, the second mixing time is 3 to 5 min, and the third mixing time is 6 to 8 min.
[0023] Further, the discharge temperature is 160°C to 170°C. Preferably, the discharge temperature is 165°C to 168°C.
[0024] Furthermore, the time of the open refining and pressing is 4 to 5 minutes. Preferably, the time of the open refining and pressing is 4.5 minutes.
[0025] Furthermore, the temperature of the feeding section of the extruder is 40°C to 45°C, the temperature of the plasticizing section is 45°C to 50°C, and the temperature of the die head is 40°C to 45°C.
[0026] Furthermore, the screw temperature of the extruder is 35°C to 40°C.
[0027] Furthermore, the temperatures of the zones of the foaming furnace are: 140±2°C for zone one, 135±2°C for zone two, 145±2°C for zone three, 150±2°C for zone four, 155±2°C for zone five, 160±2°C for zone six, and 170±2°C for zone seven.
[0028] Furthermore, after cooling, the steps of cutting, packaging and warehousing are also included.
[0029] Compared with the prior art, the beneficial technical effects of the present invention are:
[0030] The green non-corrosive rubber-plastic thermal insulation material of the invention does not contain chloride ions and elemental sulfur, which can prevent them from corroding metals, thus solving the problem of rubber-plastic products corroding metals. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The present invention will be further described below in conjunction with the accompanying drawings.
[0032] Figure 1 The present invention is a process flow chart for preparing the green and non-corrosive rubber-plastic thermal insulation material. DETAILED DESCRIPTION
[0033] The present invention provides a green non-corrosive rubber-plastic thermal insulation material, comprising the following raw materials in parts by weight:
[0034] 13-16.5 parts of nitrile rubber, 8-10.5 parts of EVA, 9-13 parts of azodicarbonamide, 9-12 parts of maleic anhydride grafted PE, 1.5-3.5 parts of carbon black, 0.3-0.5 parts of stearic acid, 0.2-0.5 parts of calcium stearate, 0.1-0.3 parts of zinc oxide, 1.5-2.5 parts of vulcanizing agent, 2-3 parts of polyethylene glycol, 2-3.5 parts of paraffin, 1-3 parts of paraffin oil, 0.2-0.5 parts of antioxidant, 0.3-0.6 parts of accelerator, 36-46 parts of flame retardant;
[0035] The flame retardant comprises the following raw materials in parts by weight: 1-3 parts of antimony trioxide, 15-18 parts of methyl dimethyl phosphate, and 20-25 parts of aluminum hydroxide.
[0036] In flame retardant materials, halogen compounds can increase the oxygen index of the material by hindering the spread of flames, inhibiting smoke generation and reducing the heat release of flames, making the material more difficult to burn. The product of the present invention does not contain halogens, and its oxygen index is greatly reduced. Aluminum hydroxide is used as a filler, but it has a flame retardant effect itself. Methyl dimethyl phosphate is added to the formula to form aluminum phosphate with aluminum hydroxide, which can improve the quality of the carbon layer and prolong the retention of volatile cracking products in the carbon layer, thereby improving the flame retardant properties of the material.
[0037] In one embodiment, the mass ratio of the nitrile rubber to the EVA is (2-3):(1.5-2).
[0038] In one embodiment, the VA content of the EVA is 12% to 16%.
[0039] In the present invention, EVA and nitrile rubber are selected as aggregates, wherein EVA is a random copolymer of ethylene and vinyl acetate. Due to the introduction of short branches formed by polar acetate groups in the ethylene chain, the original crystal state is changed, so that EVA has good flexibility and elasticity. Affected by the VA content, the polarity of different types of EVA is different. In general, EVA resins with VA content reaching more than 40% can be compatible with polar rubbers to prepare products, but their product foaming performance is not good and their comprehensive performance is poor. And EVA with VA content of 12% to 16% can manufacture foam plastics of high multiple and independent bubble type, but affected by the material polarity, its compatibility with nitrile rubber is not good, and the good dispersion of auxiliary agents cannot be achieved. Therefore, adopting EVA and nitrile rubber as aggregates, it is difficult to prepare high-performance rubber-plastic thermal insulation materials.
[0040] To this end, the present invention adds a certain amount of maleic anhydride grafted PE to the raw materials to improve the compatibility of EVA with a VA content of 12% to 16% and nitrile rubber and the dispersibility of the additive in the aggregate. At the same time, by grafting maleic anhydride molecules on the polyethylene molecular chain, the product can have both the good processability and other excellent properties of polyethylene and the reactivity and strong polarity of maleic anhydride polar molecules, thereby obtaining a stable blend and preparing a rubber-plastic thermal insulation material with good elasticity and stiffness.
[0041] In one embodiment, the antioxidant is antioxidant 4010.
[0042] In one embodiment, the vulcanizing agent is BIPB.
[0043] The present invention uses BIPB as a vulcanizing agent, wherein the peroxide bond undergoes homolytic cleavage reaction when heated to generate alkoxy free radicals, which capture hydrogen atoms from the polymer chain to generate stable peroxide decomposition products and polymer free radicals, and the two polymer free radicals combine to form a carbon-carbon crosslinking bond. The carbon-carbon bond has high bond energy, high thermochemical stability, excellent resistance to thermal oxidation aging, and no vulcanization reversion phenomenon.
[0044] In one embodiment, the accelerator is one or both of accelerator DB and accelerator DM.
[0045] In one embodiment, the accelerator is composed of accelerator DB and accelerator DM in a mass ratio of 2:1.
[0046] The combined use of accelerator DM and accelerator DB is suitable for the cross-linking system of the present invention, and can increase the cross-linking density and strength between molecular chains, and does not contain nitrosamines, does not bloom, and has good environmental protection.
[0047] Another object of the present invention is to provide a method for preparing the green, non-corrosive rubber-plastic thermal insulation material, which specifically comprises the following steps:
[0048] S1, putting nitrile rubber, EVA, and maleic anhydride grafted PE into an internal mixer for primary mixing, then putting antimony trioxide, carbon black, stearic acid, calcium stearate, methyl dimethyl phosphate, polyethylene glycol, antioxidant, aluminum hydroxide, BIPB, and paraffin into an internal mixer for secondary mixing, finally mixing azodicarbonamide and paraffin oil for a third time, then discharging, opening the mixer for tabletting and cooling to obtain material No. 1;
[0049] S2, putting the No. 1 material into an internal mixer, adding zinc oxide and accelerator, mixing and mixing, and then entering an open mixer, cutting into strips to obtain No. 2 material;
[0050] S3, extruding and molding the No. 2 material, foaming it, and cooling it to obtain a green, non-corrosive rubber-plastic thermal insulation product.
[0051] In one embodiment, the first mixing time is 1 to 3 min, the second mixing time is 3 to 5 min, and the third mixing time is 6 to 8 min.
[0052] In one embodiment, the discharge temperature is 160°C to 170°C.
[0053] In one embodiment, the discharge temperature is 165°C to 168°C.
[0054] In one embodiment, the refining and pressing time is 4 to 5 minutes.
[0055] In one embodiment, the mixing and pressing time is 4.5 min.
[0056] In one embodiment, the temperature of the extruder feeding section is 40°C-45°C, the temperature of the plasticizing section is 45°C-50°C, and the temperature of the die head is 40°C-45°C.
[0057] In one embodiment, the extruder screw temperature is 35°C to 40°C.
[0058] In one embodiment, the temperatures of the zones of the foaming furnace are: zone one 140±2°C, zone two 135±2°C, zone three 145±2°C, zone four 150±2°C, zone five 155±2°C, zone six 160±2°C, zone seven 170±2°C.
[0059] In one embodiment, the cooling process further includes cutting, packaging and warehousing.
[0060] The technical solution provided by the present invention is further described below in conjunction with embodiments.
[0061] Example 1
[0062] A green, non-corrosive rubber-plastic thermal insulation material, composed of the following raw materials in parts by weight:
[0063] 14.5 parts of nitrile rubber, 8.5 parts of EVA, 12 parts of azodicarbonamide, 10 parts of maleic anhydride grafted PE, 1.3 parts of antimony trioxide, 1.8 parts of carbon black, 0.35 parts of stearic acid, 0.25 parts of calcium stearate, 0.15 parts of zinc oxide, 16.3 parts of methyl dimethyl phosphate, 2 parts of vulcanizing agent BIPB, 2.3 parts of polyethylene glycol, 3.1 parts of paraffin, 0.3 parts of antioxidant 4010, 0.35 parts of accelerator, 2.8 parts of paraffin oil, 24 parts of aluminum hydroxide;
[0064] The VA content of the EVA is 14%; the accelerator is composed of accelerator DB and accelerator DM in a mass ratio of 2:1.
[0065] The steps of the preparation method of the material are as follows:
[0066] S1, weigh the raw materials according to the proportion, first discharge, put the nitrile rubber, EVA, maleic anhydride grafted PE into the internal mixer and mix for 1 min, then discharge for the second time, add antimony trioxide, carbon black, stearic acid, calcium stearate, methyl dimethyl phosphate, polyethylene glycol, antioxidant, aluminum hydroxide, BIPB, paraffin into the internal mixer and mix for 3 min, finally discharge for the third time, put azodicarbonamide and paraffin oil into the internal mixer and mix for 6 min, and when the temperature of the rubber material reaches 163°C, discharge the material, open the mixer and press the sheet to cool to obtain material No. 1;
[0067] S2, put the No. 1 material into an internal mixer, add all the zinc oxide and accelerator, and mix for 6.5 min. After the rubber temperature reaches 105°C, mix for 4.5 min, and then cut into strips to obtain No. 2 material;
[0068] S3, feeding the No. 2 material into the extruder for extrusion molding, the extruder temperature is set to a feeding section temperature of 42 ° C, a plasticizing section temperature of 45 ° C, a head temperature of 42 ° C, and a screw temperature of 35 ° C; the foaming furnace is divided into 7 zones according to the temperature control, and the temperatures of the foaming furnace zones are: zone 1 140 ° C, zone 2 135 ° C, zone 3 145 ° C, zone 4 150 ° C, zone 5 155 ° C, zone 6 160 ° C, zone 7 170 ° C;
[0069] S4. The foamed products in the foaming furnace are cooled by air, cut into required sizes after cooling, and packed for storage.
[0070] Example 2
[0071] A green, non-corrosive rubber-plastic thermal insulation material, composed of the following raw materials in parts by weight:
[0072] 14 parts of nitrile rubber, 9.5 parts of EVA, 11.5 parts of azodicarbonamide, 10.5 parts of maleic anhydride grafted PE, 2 parts of antimony trioxide, 2.5 parts of carbon black, 0.4 parts of stearic acid, 0.3 parts of calcium stearate, 0.2 parts of zinc oxide, 16.5 parts of methyl dimethyl phosphate, 1.6 parts of BIPB, 2.5 parts of polyethylene glycol, 2.7 parts of paraffin, 0.4 parts of antioxidant 4010, 0.4 parts of accelerator, 2 parts of paraffin oil, 23 parts of aluminum hydroxide;
[0073] The VA content of the EVA is 12.5%; the accelerator is composed of accelerator DB and accelerator DM in a mass ratio of 2:1.
[0074] The steps of the preparation method of the material are as follows:
[0075] S1, weigh the raw materials according to the proportion, first discharge, put the nitrile rubber, EVA, maleic anhydride grafted PE into the internal mixer and mix for 2 min, then discharge for the second time, add antimony trioxide, carbon black, stearic acid, calcium stearate, methyl dimethyl phosphate, polyethylene glycol, antioxidant, aluminum hydroxide, BIPB, paraffin into the internal mixer and mix for 3.5 min, finally discharge for the third time, put azodicarbonamide and paraffin oil into the internal mixer and mix for 7 min, and when the temperature of the rubber compound reaches 165°C, discharge the material, open the mixer and press the tablet to cool to obtain material No. 1;
[0076] S2, put material No. 1 into an internal mixer, add all the zinc oxide and accelerator, mix for 6.5 minutes, and then mix for 4.5 minutes after the temperature of the rubber reaches 105°C, and then cut into rubber strips to obtain material No. 2;
[0077] S3, feeding the No. 2 material into the extruder for extrusion molding, the extruder temperature is set to 43 ° C for the feeding section temperature, 47 ° C for the plasticizing section temperature, 40 ° C for the die head temperature, and 38 ° C for the screw temperature; the foaming furnace is divided into 7 zones according to the temperature control, and the temperatures of the foaming furnace zones are: 138 ° C for zone 1, 132 ° C for zone 2, 143 ° C for zone 3, 148 ° C for zone 4, 153 ° C for zone 5, 158 ° C for zone 6, and 168 ° C for zone 7;
[0078] S4. The foamed products in the foaming furnace are cooled by air, cut into required sizes after cooling, and packed for storage.
[0079] Example 3
[0080] A green, non-corrosive rubber-plastic thermal insulation material, composed of the following raw materials in parts by weight:
[0081] 13 parts of nitrile rubber, 10 parts of EVA, 10.5 parts of azodicarbonamide, 11 parts of maleic anhydride grafted PE, 1 part of antimony trioxide, 3 parts of carbon black, 0.45 parts of stearic acid, 0.4 parts of calcium stearate, 0.25 parts of zinc oxide, 17 parts of methyl dimethyl phosphate, 2.35 parts of BIPB, 2.1 parts of polyethylene glycol, 2.2 parts of paraffin, 0.25 parts of antioxidant 4010, 0.5 parts of accelerator, 2.5 parts of paraffin oil, and 23.5 parts of aluminum hydroxide;
[0082] The VA content of the EVA is 15.5%; the accelerator is composed of accelerator DB and accelerator DM in a mass ratio of 2:1.
[0083] The steps of the preparation method of the material are as follows:
[0084] S1, weigh the raw materials according to the proportion, first discharge, put the nitrile rubber, EVA, maleic anhydride grafted PE into the internal mixer and mix for 2.5 min, then discharge for the second time, add antimony trioxide, carbon black, stearic acid, calcium stearate, methyl dimethyl phosphate, polyethylene glycol, antioxidant, aluminum hydroxide, BIPB, paraffin into the internal mixer and mix for 4 min, finally discharge for the third time, put azodicarbonamide and paraffin oil into the internal mixer and mix for 6.5 min, and when the temperature of the rubber compound reaches 168°C, discharge the material, open the mixer and press the tablet to cool to obtain material No. 1;
[0085] S2, put the No. 1 material into an internal mixer, add all the zinc oxide and accelerator, put them into the internal mixer and mix for 6.5 minutes, after the rubber temperature reaches 105°C, mix for 4.5 minutes, and then cut into strips to obtain No. 2 material;
[0086] S3, feeding the No. 2 material into the extruder for extrusion molding, the extruder temperature is set to 43°C for the feeding section temperature, 47°C for the plasticizing section temperature, 40°C for the die head temperature, and 38°C for the screw temperature. The foaming furnace is divided into 7 zones for temperature control, and the temperatures of the zones are: 142°C for zone 1, 137°C for zone 2, 147°C for zone 3, 152°C for zone 4, 157°C for zone 5, 162°C for zone 6, and 172°C for zone 7.
[0087] S4. The foamed products in the foaming furnace are cooled by air, cut into required sizes after cooling, and packed for storage.
[0088] Comparative Example 1
[0089] Same as Example 1, except that no maleic anhydride-grafted PE was added.
[0090] Comparative Example 2
[0091] Same as Example 1, except that the mass ratio of accelerator DB to accelerator DM is 1:1.
[0092] Comparative Example 3
[0093] Same as Example 1, except that the ratio of accelerator DB to accelerator DM is changed to 3:1.
[0094] Comparative Example 4
[0095] Same as Example 1, except that only accelerator DB is used.
[0096] Comparative Example 5
[0097] Same as Example 1, except that only accelerator DM is used.
[0098] Comparative Example 6
[0099] Same as Example 1, except that: 14.5 parts by weight of nitrile rubber and 21.75 parts by weight of EVA.
[0100] Comparative Example 7
[0101] Same as Example 1, except that: 14.5 parts by weight of nitrile rubber and 4.83 parts by weight of EVA.
[0102] Comparative Example 8
[0103] Same as Example 1, except that BIPB is replaced by PDM.
[0104] Comparative Example 9
[0105] Same as Example 1, except that BIPB is replaced by DCP.
[0106] The product performance of the embodiment and the comparative example was tested, wherein: the product surface test was carried out according to the method described in GB / T17794-2021; the product apparent density was carried out according to the method described in GB / T6343-2009, and the qualified standard was apparent density ≤95 kg / m 3 ; The thermal conductivity of the product is tested according to the method described in GB / T10294-2008, and the qualified standard is thermal conductivity (25℃) ≤ 0.038 w / m˙K; the elemental sulfur content and chloride ion content are tested by conventional methods.
[0107] The test results are as follows:
[0108]
[0109] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A green and non-corrosive rubber-plastic thermal insulation material, characterized in that: The invention comprises the following raw materials in parts by weight: 13-16.5 parts of nitrile rubber, 8-10.5 parts of EVA, 9-13 parts of azodicarbonamide, 9-12 parts of maleic anhydride grafted PE, 1.5-3.5 parts of carbon black, 0.3-0.5 parts of stearic acid, 0.2-0.5 parts of calcium stearate, 0.1-0.3 parts of zinc oxide, 1.5-2.5 parts of vulcanizing agent, 2-3 parts of polyethylene glycol, 2-3.5 parts of paraffin, 1-3 parts of paraffin oil, 0.2-0.5 parts of antioxidant, 0.3-0.6 parts of accelerator, 36-46 parts of flame retardant; The flame retardant comprises the following raw materials in parts by weight: 1-3 parts of antimony trioxide, 15-18 parts of methyl dimethyl phosphate, and 20-25 parts of aluminum hydroxide; the vulcanizing agent is BIPB; and the accelerator is composed of accelerator DB and accelerator DM in a mass ratio of 2:
1.
2. The green, non-corrosive rubber-plastic thermal insulation material according to claim 1, characterized in that: The mass ratio of the nitrile rubber to EVA is (2-3):(1.5-2).
3. The green, non-corrosive rubber-plastic thermal insulation material according to claim 1, characterized in that: The VA content of the EVA is 12% to 16%.
4. The method for preparing the green non-corrosive rubber-plastic thermal insulation material according to any one of claims 1 to 3, characterized in that: The following steps are involved: a) putting nitrile rubber, EVA, maleic anhydride grafted PE into an internal mixer for primary mixing, then putting antimony trioxide, carbon black, stearic acid, calcium stearate, methyl dimethyl phosphate, polyethylene glycol, antioxidant, aluminum hydroxide, BIPB, and paraffin into an internal mixer for secondary mixing, and finally mixing azodicarbonamide and paraffin oil for the third time, then discharging the materials, opening the mixer for tabletting and cooling to obtain material No. 1; b) putting the No. 1 material into an internal mixer, adding zinc oxide and accelerator, mixing the material into an internal mixer, and then mixing the material into an open mixer, and cutting the material into strips to obtain the No. 2 material; c) Extruding and molding the No. 2 material, foaming it, and cooling it to obtain a green, non-corrosive rubber-plastic thermal insulation product.
5. The preparation method according to claim 4, characterized in that: The first mixing time is 1 to 3 min, the second mixing time is 3 to 5 min, and the third mixing time is 6 to 8 min.
6. The preparation method according to claim 4, characterized in that: The discharge temperature is 160°C to 170°C.
7. The preparation method according to claim 4, characterized in that: The mixing and tableting time is 4 to 5 minutes.
Citation Information
Patent Citations
Halogen-free rubber and plastic thermal insulation material and preparation method thereof
CN113621185A
Elementary sulfur free rubber thermal-insulating heat-preservation material and preparation method thereof
CN108034094A
DOP-free rubber and plastic product and preparation method thereof
CN111518323A